1989
DOI: 10.1007/bf03179641
|View full text |Cite
|
Sign up to set email alerts
|

Gel electrophoretic studies with reference to functional morphology of the salivary glands ofAcanthaspis pedestris Stal. (Insecta: Heteroptera: Reduviidae)

Abstract: Histological profile of the anterior and posterior lobes of the principal salivary and accessory glands of the reduviid Acanthaspis pedestris StaI. has been discussed in relation to enzyme pattern of the posterior lobe and the zootoxic substances of the anterior lobe as well as the protein fractions of the salivary gland lobes and the haemolymph.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 16 publications
2
11
0
Order By: Relevance
“…These authors concluded that the anterior and posterior lobes are specialised to secrete neurotoxins and digestive enzymes, respectively. Other authors have reported similar findings, albeit usually with less drastic differences between the two lobes of the main gland [ 46 , 47 ]. Only Edwards [ 6 ] observed no difference between the effects of homogenates from anterior and posterior lobes of P. rhadamanthus applied to cockroach heart-dorsum preparations.…”
Section: Evolution Of Venom Systems In Heteropterasupporting
confidence: 69%
“…These authors concluded that the anterior and posterior lobes are specialised to secrete neurotoxins and digestive enzymes, respectively. Other authors have reported similar findings, albeit usually with less drastic differences between the two lobes of the main gland [ 46 , 47 ]. Only Edwards [ 6 ] observed no difference between the effects of homogenates from anterior and posterior lobes of P. rhadamanthus applied to cockroach heart-dorsum preparations.…”
Section: Evolution Of Venom Systems In Heteropterasupporting
confidence: 69%
“…Our results contrast with those of Haridass and Ananthakrishnan 14 who injected extracts of gland compartments into prey animals, and concluded that the AMG extract contained neurotoxins while the PMG extract contained enzymes for EOD. However, other studies have found fewer functional differences between the glands using similar assays 20 , 21 , and Edwards 19 found that both PMG and AMG secretions potently paralysed cockroach heart-dorsum preparations. Apart from different assay conditions, phylogeny may explain some of these differences, as Haridass and Ananthakrishnan studied more basal ectrichodiine and peiratine assassin bugs, whereas our study and the others cited investigated more derived reduviine and harpactorine bugs.…”
Section: Discussionmentioning
confidence: 90%
“…Thus, the reduviid AMG and PMG are suggested to be specialised for secretion of neurotoxins and digestive enzymes, respectively 18 . However, other authors have found less marked or no difference between the bioactivities of AMG and PMG gland extracts 19 – 21 . We recently reported that venom obtained by electrostimulation of the assassin bug Pristhesancus plagipennis is a complex mixture of catabolic enzymes, putative cytolytic/pore-forming proteins and putatively neurotoxic disulphide-rich peptides 22 .…”
Section: Introductionmentioning
confidence: 90%
“…However, the salivary system of predatory reduviids has not been given due consideration. The salivary system of reduviids conforms to the general heteropteran plan ( Southwood 1955 ; Louis and Kumar 1973 ; Haridass and Ananthakrishnan 1981 ; Morrison 1989 ; Ambrose and Maran 1999 ; Sahayaraj et al 2010 ). The morphology of salivary glands is diverse in different subfamilies, which could be utilized as a reliable taxonomical tool ( Louis and Kumar 1973 ).…”
Section: Introductionmentioning
confidence: 82%